2004
DOI: 10.1088/0953-8984/16/11/022
|View full text |Cite
|
Sign up to set email alerts
|

Time and length scales in spin glasses

Abstract: Abstract. We discuss the slow, nonequilibrium, dynamics of spin glasses in their glassy phase. We briefly review the present theoretical understanding of the spectacular phenomena observed in experiments and describe new numerical results obtained in the first large-scale simulation of the nonequilibrium dynamics of the three dimensional Heisenberg spin glass. Why do we study spin glass dynamics?Spin glasses can be seen as one of the paradigms for the statistical mechanics of impure materials. Experimentally, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…in the Ising model 1 . Hence it appears potentially easier to detect chaotic temperature effects in Heisenberg systems than in Ising systems 44 , so this possibility needs to be investigated.…”
Section: B Is Temperature Chaos Relevant?mentioning
confidence: 99%
See 1 more Smart Citation
“…in the Ising model 1 . Hence it appears potentially easier to detect chaotic temperature effects in Heisenberg systems than in Ising systems 44 , so this possibility needs to be investigated.…”
Section: B Is Temperature Chaos Relevant?mentioning
confidence: 99%
“…Numerical studies of temperature shifts and cycles in the Ising version of the model have been reported 26,27,28,29,30,31,32,33 , and temperature cycles have been discussed theoretically 34,35,36,37,38,39,40,41,42 . However, the Heisenberg spin glass model has been much less studied than its Ising counterpart, even though it is closer to many of the experimentally studied spin glass systems, and only a few aging studies exist 1,32,43,44 . In particular, extensive studies of temperature cycles have not been reported (see Ref.…”
Section: Introduction To Basic Phenomenamentioning
confidence: 99%
“…A physical argument for the glass analogy is that the long-range interaction between dislocations can change sign as a function of relative angles, thus making frustration possible. Frustrated interactions are known to give rise to spin glasses in the presence of quenched disorder [16]. Furthermore, there is an external element of randomness in dislocation systems that arises from initial conditions.…”
mentioning
confidence: 99%